Temporary Protection Regimes and Refugees: What Works? Comparing the Kuwaiti, Bosnian, and Syrian Refugee Protection Regimes - Bastaki, Jinan (Refuge, 2018)
Many states have responded to mass influxes of refugees fleeing generalized violence and war by setting up ad hoc and/or temporary protection regimes. These regimes have had various degrees of success, depending particularly on the length of stay of the refugees. This article will compare the approach of states to three separate refugee influxes—Kuwaiti refugees in the Gulf, Bosnian refugees in Germany, and Syrian refugees in Turkey—and will argue that efforts to harmonize temporary protection measures are desirable, but given that these situations tend to be prolonged, there must be greater responsibility sharing between states, in order to lead to greater integration of refugees in the host states.